Pretreatment of Used Cooking Oil Using Avocado Seed Adsorbent for Biodiesel Production Preparation - Nasriadi Dali; Seniwati Dali; Armadi Chairunnas; Hilda Ayu Melvi Amalia; Sri Ayu Andini Puspitasari (Universitas Diponegoro, 2023)
Used cooking oil (UCO) can be used as raw material for biodiesel production, but its free fatty acid (FFA) content is still quite high, so it is necessary to do pretreatment in the form of an adsorption process to reduce FFA levels. This study aims to determine the optimum conditions for the adsorption process and determine FFA levels of UCO before and after pretreatment. The adsorbent used is avocado seed activated charcoal, because it has a surface area of 19.62 m2/g. The larger the surface area of the adsorbent material, the greater the adsorption capacity of the adsorbent. Optimization of the UCO adsorption process includes variations in adsorbent mass (6, 8, 10 g), adsorbent particle size (60, 100, 140 mesh), contact time (2, 6, 10 hours), and temperature (60, 80, 100oC). The results showed that the optimum conditions for adsorption of UCO were obtained at mass (10 g), particle size (100 mesh), contact time (6 h), and temperature (80oC). This condition can reduce the FFA content of UCO by 71.64% (w/w), from 5.29% (w/w) to 1.50% (w/w). The FFA content of UCO [1.50% (w/w)] produced after pretreatment was qualified as a raw material for the preparation of biodiesel production through the transesterification stage.